From Academic Culture to Organisational Sustainability: The Mediating Role of Faculty Performance in Higher Education - Harmon Chaniago; Hidayat Hidayat (Lembaga Bale Literasi, 2026)
This study aims to examine the influence of academic culture on organisational sustainability, with faculty performance as a mediating factor, in the context of higher education. A qualitative case study approach was employed. In this study, mediation is interpreted as an explanatory process that describes how academic culture influences organisational sustainability through faculty performance, consistent with the qualitative research design. Data were collected through semi-structured interviews with 30 faculty members from private universities and analysed using thematic analysis in NVivo 14. The findings reveal that academic culture serves as a fundamental driver shaping faculty behaviour and work orientation. Individual motivation, institutional demands, and administrative workload influence faculty performance. The key finding of this study highlights that faculty performance serves as a key mechanism connecting academic culture and organisational sustainability. Organisational sustainability is conceptualised as a multidimensional construct encompassing academic quality, governance, and innovation. This study contributes to theory by proposing a more integrated understanding of the relationship among academic culture, faculty performance, and organisational sustainability. This study contributes theoretically by integrating academic culture, faculty performance, and organisational sustainability into a comprehensive conceptual model. Practically, the findings emphasise the importance of strengthening academic culture, improving faculty performance, and enhancing leadership roles in promoting sustainability in higher education institutions, particularly in developing countries such as Indonesia